2016
DOI: 10.3390/cryst6010014
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Nitrogen-Enriched Metal Organic Frameworks with CCS Potential

Abstract: Materials with enhanced carbon capture capacities are required to advance post-combustive amelioration methods; these are necessary to reduce atmospheric carbon dioxide emissions and the associated rate of global temperature increase. Current technologies tend to be very energy intensive processes with high levels of waste produced; this work presents three new metal organic framework materials with embedded Lewis base functionalities, imparted by the nitrogen-rich ligand, demonstrating an affinity for carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…From the observed isotherm, it can be evidently concluded that the adsorption of CO 2 molecules successfully occurred on the PTOF surface (M−O 2− •••CO 2 (M = Cu, Co, Ni)), and the maximum CO 2 uptake was attained to be 1.055 mmol/g. 53,54 These results suggested that the PTOF catalyst possesses Lewis basic sites, which are well accessible and ready for the adsorption of CO 2 during the reaction transformation. Furthermore, to provide further support to the catalyst surface being negatively charged, the ζ-potential of the PTOF also showed a negative surface charge with a value of −5.3 eV.…”
Section: Characterization Of Materialsmentioning
confidence: 93%
“…From the observed isotherm, it can be evidently concluded that the adsorption of CO 2 molecules successfully occurred on the PTOF surface (M−O 2− •••CO 2 (M = Cu, Co, Ni)), and the maximum CO 2 uptake was attained to be 1.055 mmol/g. 53,54 These results suggested that the PTOF catalyst possesses Lewis basic sites, which are well accessible and ready for the adsorption of CO 2 during the reaction transformation. Furthermore, to provide further support to the catalyst surface being negatively charged, the ζ-potential of the PTOF also showed a negative surface charge with a value of −5.3 eV.…”
Section: Characterization Of Materialsmentioning
confidence: 93%
“…The main area of MOF application–gas sorption and separation arises from their inherent porosity . Two of the most promising fields in this area are methane , and hydrogen fuel storage and carbon capture and storage , both of these fields are crucial for solving the global problem of climate change . Some MOFs with good gas storage capacity, such as HKUST-1, ZIF-8, or UiO-66 are now produced on industrial scale …”
Section: Introductionmentioning
confidence: 99%
“…99,100 An original type of 1D ladder structure has also been reported by Fletcher et al with the compounds [Ni(4,4'-bptz)1.5(NO3)]•nDCM and [Co2(4,4'-bptz)3(NO3)4]•nDCM. 101 The 1D ladders pack to form a 3D network which shows a reasonable CO2 uptake. From all these results, tetrazine-based MOFs can be considered as suitable materials for gas separation and selective CO2 capture.…”
Section: 6-bis(4-pyridyl)-1245-tetrazine (44'-bptz)mentioning
confidence: 99%